2020
DOI: 10.1016/j.amepre.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Overprescribing of Opioids to Adults by Dentists in the U.S., 2011–2015

Abstract: Introduction: Dentists prescribe 1 in 10 opioid prescriptions in the U.S. When opioids are necessary, national guidelines recommend the prescription of low-dose opioids for a short duration. This study assesses the appropriate prescribing of opioids by dentists before guideline implementation. Methods: The authors performed a cross-sectional analysis of a population-based sample of 542,958 U.S. commercial dental patient visits between 2011 and 2015 within the Truven Health MarketScan Research Databases (data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…1,2 Opioid use is common among older patients given the increasing prevalence of medical conditions associated with acute and/or chronic pain, including opioids prescribed in dental settings. [3][4][5][6][7] Rates of polypharmacy are high among older patients, 8 often a result of necessary medication management of multiple comorbidities. 9 However, this is problematic due to increased risk for medication-associated adverse effects and drug-drug interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Opioid use is common among older patients given the increasing prevalence of medical conditions associated with acute and/or chronic pain, including opioids prescribed in dental settings. [3][4][5][6][7] Rates of polypharmacy are high among older patients, 8 often a result of necessary medication management of multiple comorbidities. 9 However, this is problematic due to increased risk for medication-associated adverse effects and drug-drug interactions.…”
mentioning
confidence: 99%
“…The United States is experiencing a devastating public health crisis that causes over 33,000 deaths annually related to opiate analgesics 1,2 . Opioid use is common among older patients given the increasing prevalence of medical conditions associated with acute and/or chronic pain, including opioids prescribed in dental settings 3–7 . Rates of polypharmacy are high among older patients, 8 often a result of necessary medication management of multiple comorbidities 9 .…”
mentioning
confidence: 99%
“…15 A 2020 study based on over half a million adult dental visits found that 29.3% of dental opioid prescriptions exceeded the MME-based recommendation, while 53% exceeded the recommended days' supply. 16 Hydrocodone, an opium-based analgesic, is associated with the greatest number of opioid deaths. 17 Together with oxycodone, it remains one of the most commonly prescribed medications by dentists.…”
Section: Introductionmentioning
confidence: 99%
“…The DEA production quotas from 2010 to 2020 decreased by 22.4% for codeine, 35.9% for oxycodone, 36.7% for hydrocodone, and 43.1% for fentanyl relative to only 7.7% for pentobarbital (10)(11). At the same time, there has been an increased attention to the development of more cautious prescribing practices by general practitioners (12), surgeons (13), emergency medicine specialists (14), and dentists (15).…”
Section: Introductionmentioning
confidence: 99%